Inter and intraspecific comparisons of the skeletal Mg/Ca ratios of high latitude Antarctic echinoderms. Issue 3 (13th February 2018) - Duquette, A.; Halanych, K.M.; Angus, R.A.; Mcclintock, J.B.
Abstract: Echinoderms are vulnerable to ocean acidification because of their high magnesium calcite skeletons. Here, skeletal Mg/Ca ratios were examined within and between individuals of 20 Antarctic echinoderms representative of the asteroids, ophiuroids and echinoids. The highest mean Mg/Ca ratios occurred in the discs and arms (0.111 and 0.110, respectively) of brittle-stars and the lowest in the spines (0.010) of cidaroid sea urchins. Many taxa (11 of 14 species) from the collection sites showed no intraspecific differences in Mg/Ca ratios between given skeletal components. Exceptions were the spines of two regular sea urchins and the skeletal ossicles of the combined arms and disc of a brittle-star. The relationship between skeletal magnesium content and latitude was further evaluated and an inverse correlation was found between Antarctic echinoderm taxa skeletal magnesium content and latitude across 62° to 76°, indicating that the relationship occurs over relatively narrow latitudes. Upon examination of an even narrower range (70–76° latitude), a region where the mineralogy of echinoderm skeletons has not been investigated, the predicted inverse relationship between Mg/Ca ratio and latitude was still observed in sea-stars, but not in brittle-stars or sea urchins.